What Should We Do for Jay?: The Edges of Life and Cognitive Disability - Turnbull, H. Rutherford (Journal of religion, disability & health, 2005)
This article asks who, how, and on what grounds end-of-life decisions should bemade for a personwith a significant cognitive disability (the author's son). It argues that the decisions must be based on principled grounds and that those grounds are both legal (the core concepts of disability policy and the appropriate case law). It describes how five different “models” of thinking about disability affect our decision-making, and how those models reflect as much about the decision-makers as about people with disabilities. It next poses the paradox that we may make the right decision for the wrong reason, or the wrong decision for the right reason. Finally, it argues that we should yield to the paradoxes, affirm but move beyond rights, and embrace trust and compassion as supplementary grounds for decision-making.